Implementasi Peraturan Daerah Kota Pekanbaru Nomor 8 Tahun 2012 Tentang Retribusi Izin Gangguan (Studi Izin Gangguan Warung Internet di Kecamatan Tampan): Universitas Islam Riau - Sobri Sobri; Muhammad Husaini (UIR PRESS, 2018)
Inscrease revenue in pekanbaru city government must maximize all forms of existing licensing in order to generate income areas one of which is the levy permit interfence. Therefore, pekanbaru city government issued local Regulation No 8 of 2012 on disturbance Permit. Of a number of types of businesses that should have this permit, one of which is the internet cafes. Public internet, or commonly abbreviated café is one form of business managed by groups or individuls that provide services in the form of internet services by users. But in pelaksanaan, still less the maximum. Still many businesses,especially in sub handsome café that does not take care of this permit as mandated by local regulation. The purpose of this study was to determine the implementation of regional regulation pekanbaru 8 year 2012 on permits impaired against permit internet cafes in district charming and identify factors inhibiting the implementation of regional regulation pekanbaru 8 year 2012 on permits impaired against permit internet cafes in district charming. In accordance with the problems of the type of research is descriptive survey using quantitative methods. As for the population in this study is the head of the integrated licensing service agency investment and pekanbaru, employees of the division of licensing, as well as the owner of the café in the district charming. The results showed bahwasanya implemention Regional regulation pekanbaru No. 8 of 2012 on permits impaired against permit internet cafes in sub handsome is in the category fairly implemented, this can be seen from the four indicators that have been the outhor set that communication, resources, disposition and structure bureaucracy with the recapitulation as much as 50%. Implementation of the inhibiting factors in pekanbaru city regional regulation No. 8 of 2012 on agains nuisance permits business licenses in district handsome public internet is the lack of socialization, lack of human resources and lack of infrastructure tu support the implemtation of these regulations.